Investigation of Insulator Performance Under Artificial Contaminants - Negara, I M. Yulistya; Asfani, Dimas; Hernanda, IGN Satriyadi; Fahmi, Daniar; Ksatria, Arief; S. H. Hutabarat, Ariel Kevin (International Journal of Integrated Engineering, 2023)
There are three types of insulators, namely glass, ceramic, and polymer. Although polymers have hydrophobic properties that make them superior to other materials. However, in its application, ceramic and glass insulators are still used because they are cheaper. Environmental conditions around the work location of the insulator greatly affect its performance. Areas with high levels of pollution will result in the insulator being damaged quickly. The effect of seawater and fly-ash contaminants on the three types of insulators is discussed in this study. Experimental approaches and FEM-based simulations have been carried out. Pollution levels in seawater contaminants were standardized using ESDD. Meanwhile, the level of pollution in fly-ash contaminants is standardized using NSDD. Simulations and experiments were carried out at four levels of contamination, namely light, medium, heavy and very heavy. Then the simulation and test results are compared. The greater the ESDD and NSDD values, the greater the leakage current.